The Influence of Atorvastatin, Amlodipine and Ethoxidol on Ubiquinol and Ubiquinone Endogenous Plasma Concentrations in Patients with Chronic Heart Failure - Zozina, V.I.; Kondratenko, S.N.; Shikh, E.V.; Krasnykh, L.M.; Melnikov, E.S.; Kukes, V.G. (Current Drug Metabolism, 2023)
Background: Coenzyme Q10 is a key component of the mitochondrial respiratory chain and a fat-soluble endogenous antioxidant performing many vital functions in the human body. Many researchers studied the plasma concentrations of ubiquinol, ubiquinone, total CoQ10 and the redox state (ubiquinol/ubiquinone ratio) of CoQ10 in healthy volunteers. However, these parameters in the plasma of patients with chronic heart failure (CHF) remain almost uninvestigated.Objective: The aim of this case-control study was to investigate the effect of atorvastatin, amlodipine and ethoxidol on endogenous plasma concentrations of ubiquinol, ubiquinone, total CoQ10 and its redox state in patients with CHF.Methods: The study included 62 patients with CHF divided into four groups depending on the prescribed therapy. For the quantitative determination of ubiquinol, ubiquinone, and total CoQ10 in the plasma of patients, HPLCMS/ MS was used.Results: It was established that the endogenous plasma concentration of total CoQ10 in patients with CHF is significantly lower than in healthy volunteers, and the ratio of reduced and oxidized forms of CoQ10 is shifted towards ubiquinone. It was a statistically significant effect of drugs with different physicochemical structures and pharmacological action on the plasma concentrations of ubiquinol, ubiquinone and total CoQ10: atorvastatin administration led to a decrease in the concentration of ubiquinol (-33.3Δ%), and total CoQ10 (-15Δ%), administration of amlodipine contributed to an increase in the levels of ubiquinol (+27.7Δ%) and total CoQ10 (+18.2Δ%), and the administration of ethoxidol caused an increase in the concentration of ubiquinol (+25Δ%), ubiquinone (+17.7Δ%) and total CoQ10 (+20.2Δ%).Conclusion: Amlodipine is able to neutralize the negative effect of atorvastin on the redox balance of CoQ10 in patients with CHF. An additional prescription of the antioxidant ethoxidol to standard therapy for patients with CHF was substantiated. Determination of the redox state of CoQ10 in plasma can be used to diagnose and assess the degree of oxidative stress in patients with cardiovascular diseases, as well as to assess the efficacy and safety of ongoing pharmacotherapy.
Keywords: amlodipine